Analisis Kualitas Website Resmi Penanggulangan Covid-19 di Indonesia Dengan Menggunakan Metode Pieces - Annas Luthfi Hibatullah; Diana Khuntari (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2022)
The existence of the internet is inseparable from the life of modern society that relies on it as the primary source for information, such as websites. The use of the website is one of the government's efforts to disseminate information about Covid-19. Then Indonesia Government has covid19.go.id, an official website that becomes the major source for Covid-19 information. One of the determinants for the information quality is the website quality as a medium for that information. Thus, this study aims to analyze the quality of the Covid-19 countermeasures website. This study used descriptive qualitative method and collected data through interviews, observation, and documentation. The approach used to analyze the website quality is PIECES which consists of 6 indicators, namely: Performance, Information, Economy, Control, Efficiency, and Service. The resource person for this research is a system analyst working for National Disaster Mitigation Agency (BNPB) and for the Covid-19 Task Force to manage the Covid-19 website. The results of the study using the 6 PIECES indicators show that: 1) the website has a performance with a value of C or average because the size of the website is quite large and the loading time is 3.7 seconds, however, no errors are found; 2) the information presented is complete, useful, and in line with the visitors needs; 3) economically, the website has a positive impact on society and for entrepeneur to adapt their business to the existing regulations; 4) control of the website is carried out by several parties and the website has also achieved three international certificates from three different institutions; 5) in terms of efficiency, the website functions properly, but there are several features that cannot be used; 6) the website service is good since it provides a comfortable browsing experience. To improve the quality of the website, it is necessary to increase performance and improve several features.